2019
DOI: 10.1071/an17804
|View full text |Cite
|
Sign up to set email alerts
|

Sexual precocity and productivity of beef cattle female under grazing conditions

Abstract: In view of the importance of female reproductive traits as a key profit indicator in beef-cattle production systems, the objective of the present study was to explore the relationships between female sexual precocity and potential predictive traits of easy and early measurement, related to the productive and reproductive efficiency. Heifers born in 2011 and 2012 (n = 132) from five genetic groups (Angus, Hereford, Angus-Hereford, Hereford-Angus and Argentine Creole) in 2 years (Trial 1 and Trial 2) under grazi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
0
2
0
2
Order By: Relevance
“…(Swiestra et al, 1977). In others meat breeds, the age at puberty was 464.6 in Angus, 478.6 in Hereford and 493.3 in Creole breed (Pardo et al, 2018).…”
Section: Discussionmentioning
confidence: 94%
“…(Swiestra et al, 1977). In others meat breeds, the age at puberty was 464.6 in Angus, 478.6 in Hereford and 493.3 in Creole breed (Pardo et al, 2018).…”
Section: Discussionmentioning
confidence: 94%
“…The RAB11FIP5 and SFXN5 genes have already been described as associated with shear force [ 56 ], a method used to evaluate the tenderness of meat. There is a high degree of interdependence of puberty traits and growth and body composition [ 57 ]. Pacheco et al [ 58 ] reported that subcutaneous fat thickness is favored when younger animals are slaughtered.…”
Section: Resultsmentioning
confidence: 99%
“…La información disponible indica que se requiere un mínimo de grasa corporal para detonar procesos reproductivos como la PB en vaquillas (9) y un mínimo de CC (54) . En un estudio (55) realizado en vaquillas Nelore, se encontraron altas correlaciones (de 0.82 a 0.93) entre la CC y el GD, y se afirmó que con la CC se puede predecir el GD en ganado B. taurus indicus en las diferentes etapas del ciclo de producción.…”
Section: Discussionunclassified
“…Se ha reportado que las concentraciones circulantes de leptina aumentan durante el desarrollo puberal en vaquillas (8) . La información disponible sugiere que hay un nivel crítico de grasa requerido para el inicio de la actividad reproductiva (9) y que puede haber diferencias en este límite crítico de grasa entre razas (10) , lo que implica que deben existir condiciones para regular la acumulación de energía excedente en forma de grasa corporal. A pesar de que se conocen varios factores que afectan el establecimiento de la pubertad en vaquillas, es escasa la literatura sobre las interacciones entre estos y, particularmente, sobre las diferencias entre B. taurus taurus y B. taurus indicus, en especial si consideramos el factor estacionalidad, que se asocia con el ganado Cebú (3,11,12) .…”
Section: Introductionunclassified